Odpowiedzi

2009-12-03T15:49:10+01:00
(a-b)(a+b)=a²-b²
a) (√5-√3)(√5+√3)=5-3=2
b) (√7+4)(4+√7)=16-8√7+7=23-8√7
c) (√11+2)(√11-2)=11-2=9
d) (2√2-1)(2√2+1)=8-1=7
e) (√15-√6)(√5-√2)=√75-√30-√30+√12=5√3-2√30+2√3=7√3-2√30
f) (√20-√18)(√20+√18)=20-18=2
2009-12-03T15:51:43+01:00
@up
Kolega wyżej podał złą odp w c) :>


a)
(√5-√3)(√5+√3) = 5-3 = 2
b)
(√7+4)(4+√7) = 7 + 8√7 + 16 = 23 + 8√7
c)
(√11+2)(√11-2) = 11 - 4 = 7
d)
(2√2-1)(2√2+1) = 4*2 - 1 = 8-1 = 7
e)
(√15-√6)(√5-√2) = √3(√5-√2)(√5-√2) = √3(5 - 2√10 +2) = 5√3 - 2√30 +2√3 = 7√3 - 2√30
f)
(√20-√18)(√20+√18) = 20 - 18 = 2
Najlepsza Odpowiedź!
2009-12-03T15:51:48+01:00
Używam wzoru skróconego mnożnenia: (a+b)(a-b)=a²-b²
a) (√5-√3)(√5+√3)=5-3=2
b) tu zapewne miał być minus:
(√7+4)(4-√7)=4²-7=16-7=9
c) (√11+2)(√11-2)=11-2²=7
d) (2√2-1)(2√2+1)=2²*2-1²=8-1=7
e) (√15-√6)(√5-√2)=√80-√30-√30+√12=√80-2√30+√12
f) (√20-√18)(√20+√18)=20-18=2